Modulation of energy and protein supplies in sequential feeding in laying hens. (5th September 2014) - Traineau, M.; Bouvarel, I.; Mulsant, C.; Roffidal, L.; Launay, C.; Lescoat, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Sequential feeding (SF) consists of splitting energy (E) and protein/calcium (P) fractions temporally, improving the feed conversion ratio (FCR) of hens compared with a continuous distribution during the day. In a previous study, the E fraction (with a low level of protein) was provided in the morning, whereas the P fraction (with low level of energy) was given in the afternoon. However, there is no clear evidence that a requirement in energy or proteins is connected to these distribution sequences, whereas the requirement for calcium is known to be required in the afternoon. To evaluate the effects on performances of the modulation of energy and protein supplies in SF, five different sequential treatments were offered: E0P0/E0P0; E+P+/E−P−; E+P−/E−P+; E0P+/E0P− and E+P0/E−P0 where E+ represents a high energy level, E0 a moderate one and E− a low one (with the same meaning for P regarding protein supply). Afternoon fractions were provided with particulate calcium. A total of 168 Hendrix hens were housed in individual cages from 20 to 39 weeks of age in two environmentally contrasted rooms. Feed intake in the morning and afternoon fractions, egg production, egg weight, BW and weight of digestive organs were recorded. No diet effect was observed concerning feed intake, egg production and BW. These results suggested that hens are not able to fit their feed intake on energy or protein level of fractions within half-day duration, whereas at the day scale same protein and energy intakes were observed. Moreover, the time of nutrient distribution in feeding did not seem to have an impact on birds' performances. These studies have also demonstrated that, despite strong environmental pressure, the hens with SF had attenuated performance but continue to produce eggs.